Problematika dan Strategi Pembelajaran Pendidikan Agama Islam Berbasis TIK - Wahyu Pambudi, Giri; Hafidz, Hafidz (Educatio, 2025)
Islamic Religious Education (PAI) faces various challenges in the digital era, ranging from limited infrastructure and access to technology to low teacher competence and doubts about the suitability of digital content with Islamic values. This article aims to identify the main problems in the implementation of Information and Communication Technology (ICT)-based PAI learning and formulate practical strategies to overcome them. The method used is a literature review of various empirical studies and current theories on the use of ICT in PAI, complete with case examples of implementation in various Islamic educational institutions. The results of the study indicate six main obstacles: (1) uneven accessibility and ICT infrastructure, (2) limited teacher ability to utilize technology, (3) concerns about the negative impact on religious values, (4) challenges in replicating digital religious experiences, (5) students' digital literacy gaps, and (6) inadequate evaluation of the impact of ICT integration. To overcome this, recommended strategies include developing supportive policies, ongoing training for teachers, utilizing interactive platforms and media, curating quality digital content, implementing a blended learning model, and collaboration between schools, parents, and stakeholders. This article concludes that ICT integration in PAI can improve the effectiveness and accessibility of learning as long as it is supported by commitment, resources, and a clear policy framework.